Recovery profile of anaerobic ammonium oxidation (anammox) bacteria inhibited by ZnO nanoparticles - AKGÜL, DENİZ (IWA PUBLISHING, 2022)
The potential effects of nanoparticles (NPs) on biological treatment processes have become significant due to their increasing industrial applications. The purpose of this research was to investigate the self-recovery ability of anammox bacteria following to acute ZnO NPs toxicity. In this context, a 2-liter lab-scale anammox reactor was operated for 550 days to enrich the biomass required to the batch exposure tests. Anammox culture was firstly exposed to four different doses of ZnO NPs (50, 75, 100 and 200 mg/L) for 24 h. Then, the ZnO NPs were removed and self-recovery performance of the anammox bacteria was assessed by evaluating the nitrogen removal capacities for 72 h. Besides the nitrogen removal performance, extracellular polymeric substances (EPS) production was also detected to deeply understand the response of the enriched anammox culture against ZnO NPs exposure. The results revealed that, sudden and high load of ZnO NPs (100 and 200 mg/L) resulted in persistent impairment on the nitrogen removal performance of the enriched anammox culture. However, relatively lower doses (50 and 75 mg/L) caused deceleration of the nitrogen removal performance during the recovery period. In addition, EPS content in the reactor decreased along with escalating load of ZnO NPs.
Keywords: acute inhibition; anammox bacteria; extracellular polymeric substances; nanoparticle toxicity; self-recovery; zinc oxide nanoparticles; METAL-OXIDE NANOPARTICLES; WASTE-WATER; HEAVY-METALS; NITROGEN REMOVAL; GRANULAR SLUDGE; CU; PERFORMANCE; IMPACTS; CEO2